Pengaruh Leverage, Likuiditas, Dan Profitabilitas Terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Indriyani, Nova; Mahpudin, Endang (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to test the effect of leverage, liquidity, and profitability on tax aggressiveness in food and beverage sub-sector companies listed on the IDX during the 2019-2023 period. The research sample consists of 120 data selected using the purposive sampling method. Multiple linear regression analysis is used to test the effect of independent variables on tax aggressiveness. The findings of the analysis show that leverage has no significant effect on tax aggressiveness, while liquidity and profitability have a significant effect on tax aggressiveness.